Corporate Legal Practicums Determine Graduate Competencies In Indonesian Higher Education: Praktikum Hukum Perusahaan Menentukan Kompetensi Lulusan Pada Pendidikan Tinggi Indonesia - Aji Pangestu; Noor Fatimah Mediawati (International Consortium of Education and Culture Research Studies, 2025)
General Background Internship programs constitute an integral component of the Indonesian higher education system designed to connect academic theory with professional practice under current national policies. Specific Background Universitas Muhammadiyah Sidoarjo collaborates with PT Mitra Usaha Propertindo to supply law students with relevant corporate operational experiences. Knowledge Gap Students frequently encounter misaligned tasks limited to basic administrative duties, creating a perception of practicums as mere formalities and risking severe professional deskilling. Aims This study evaluates a targeted legal training framework to guarantee optimal alignment between academic disciplines and workforce skill requirements. Results Observational evaluations indicate that participants actively execute technical duties including drafting legal documents, analyzing corporate contracts, and managing legal archives. Furthermore, intensive mentorship and constructive feedback from corporate supervisors significantly develop both the technical legal abilities and non-technical communication skills of the participants. Novelty This research demonstrates a highly specific integration model successfully resolving the persistent academic-industry task misalignment within university legal studies. Implications Academic institutions and industry partners must establish continuous evaluation systems and ensure strict task relevance to secure future workforce readiness and maximize mutual institutional benefits. Highlights: Industry mentorship directly builds technical contract analysis and document drafting abilities. Task alignment prevents deskilling and meaningless administrative assignments during student placements. Continuous academic evaluations guarantee relevant practical experiences for university scholars. Keywords: Industry Collaboration, Contract Analysis, Academic Synergy, Document Drafting, Skill Alignment